The Influence of the Technology-Based Mind Mapping Learning Model on Students’ Critical Thinking Abilities Reviewed from a Gander Perspective - Dandi Ansyah; Melly Novalia; Pratama Benny Herlandy (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study examines the effect of a technology-based Mind Mapping learning model on students' critical thinking skills, focusing on gender differences. Conducted at Al-Amin Secondary School in Malaysia with 25 eighth-grade students (13 male, 12 female), the research utilized a pre-test and post-test experimental design. Results showed that after applying the Mind Mapping model, both male and female students improved their critical thinking, with females achieving higher scores. Male students' average score increased from 7.08 to 11.38, while females' scores rose from 9.33 to 13.42. The paired sample t-test confirmed significant improvement (t = 12.860, p < 0.05). The findings highlight the positive impact of Mind Mapping in enhancing critical thinking, particularly in teaching social media ethics, with female students showing better results.